Contesting Genocide: South Africa’s Legal Standing and International Court of Justice’s Reach Over Israel - Asasiyah, Aulia Randits Maulida; Danial, Danial; Vitrana, Mokhamad Gisa; Hambali, Hambali; Anom, Surya (Tirtayasa Journal of International Law, 2025)
The lawsuit filed by South Africa against Israel regarding alleged acts of genocide against Palestinians, submitted to the International Court of Justice (ICJ) on December 29, 2023, raises a central legal issue concerning South Africa’s legal standing under Article IX of the 1948 Genocide Convention and the Statute of the ICJ. This study adopts a normative juridical approach using a case study method with descriptive-analytical specifications, based on secondary data obtained through literature review. The analysis is grounded in international legal theory, particularly the jurisdiction of international courts and the principle of obligations erga omnes partes. The results show that South Africa holds legal standing to bring the case, as the Genocide Convention grants all State Parties the right to raise disputes regarding violations, regardless of direct involvement. However, the ICJ’s jurisdiction remains contingent upon mutual consent, which Israel has denied. This rejection poses a barrier to judicial resolution. Therefore, South Africa may need to pursue diplomatic and multilateral efforts to secure jurisdictional recognition and strengthen evidentiary claims related to the alleged acts of genocide. This research contributes to the scholarly discourse by reinforcing the applicability of the erga omnes partes principle in genocide-related disputes and by offering a legal analysis of jurisdictional constraints at the ICJ, thus providing a valuable reference for understanding third-party state standing and the enforcement limits of international adjudication in politically sensitive cases.